2006
DOI: 10.1111/j.1748-121x.2006.00021.x
|View full text |Cite
|
Sign up to set email alerts
|

Safe in their hands? Britain’s Law Lords and human rights

Abstract: This paper, which is the revised text of the first Stephen Livingstone Memorial Lecture delivered in February 2006, surveys the human rights jurisprudence of the House of Lords over the past 10 years. It considers not just how the Law Lords have responded to the Human Rights Act 1998 but also how they have developed the law on equality, asylum and immigration. In assessing whether human rights are ‘safe’ in the hands of the Law Lords, it looks, first, at how willing the Law Lords have been to engage with human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…More recently, the Human Rights Act 1998 has been the major catalyst. It has imposed a legal obligation to respect Convention rights on all public bodies, provided lawyers and judges with direct recourse to the Strasbourg rights jurisprudence in any UK legal proceeding and engendered a new rights awareness among the public and media (Clayton and Tomlinson, 2009;Dickson, 2006;Leigh and Masterman, 2008).…”
Section: Human Rights As Legal Risk and Legal Risk+mentioning
confidence: 98%
“…More recently, the Human Rights Act 1998 has been the major catalyst. It has imposed a legal obligation to respect Convention rights on all public bodies, provided lawyers and judges with direct recourse to the Strasbourg rights jurisprudence in any UK legal proceeding and engendered a new rights awareness among the public and media (Clayton and Tomlinson, 2009;Dickson, 2006;Leigh and Masterman, 2008).…”
Section: Human Rights As Legal Risk and Legal Risk+mentioning
confidence: 98%
“…67 Dickson has suggested that the time has come to reconsider the traditional dualism of UK law, and to allow courts to rely on international standards where the government has indicated it intends to respect those standards. 68 Lord Steyn has even speculated that the traditional rationale for courts not to apply unincorporated international treaties does not apply in the context of human rights treaties that impose obligations on the State to respect individuals' rights. 69 It is worth noting in this regard that the Joint Committee on Human Rights, without going so far, has recommended that any Bill of Rights for the UK should allow judges to rely upon unincorporated international human rights treaties as a source of interpretation.…”
Section: Ambition: Moral Not Legal Forcementioning
confidence: 98%
“…17 A more recent study of decision-making in the House of Lords by Dickson is more relevant, but neither systematic nor quantitative. 18 Many of the more significant studies have been published outside the law journals. Goold, Lazarus and Swiney compiled a comparative survey of the HRA for the Ministry of Justice, covering the ECHR, Germany, France and Spain in addition to the UK, but which only focussed on proportionality and the issue of 'balancing' rights and security.…”
mentioning
confidence: 99%